2016
DOI: 10.1080/15592324.2016.1150403
|View full text |Cite
|
Sign up to set email alerts
|

Myrosin cells are differentiated directly from ground meristem cells and are developmentally independent of the vasculature in Arabidopsis leaves

Abstract: Myrosin cells accumulate myrosinases in their vacuoles to catalyze the production of toxic compounds when tissues are damaged by herbivores. Myrosin cells are positioned adjacent to the abaxial side of the vasculature but their origin is unclear. To determine whether the myrosin cells are differentiated from vascular precursor cells, we generated a transgenic Arabidopsis line that expressed a myrosin cell reporter together with one of 3 vascular precursor cell reporters. The myrosin-positive cells were discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…In nonfloral tissues, GUS staining was observed only in leaves (Fig. 5, A and B), where it was restricted to a patchy pattern along the vasculature, which might indicate an expression in myrosin cells (Shirakawa et al, 2016). No GUS staining was observed in any of the other vegetative tissues.…”
Section: Reporter Gene Analysis Of Stp7 Stp8 and Stp12 Expressionmentioning
confidence: 94%
“…In nonfloral tissues, GUS staining was observed only in leaves (Fig. 5, A and B), where it was restricted to a patchy pattern along the vasculature, which might indicate an expression in myrosin cells (Shirakawa et al, 2016). No GUS staining was observed in any of the other vegetative tissues.…”
Section: Reporter Gene Analysis Of Stp7 Stp8 and Stp12 Expressionmentioning
confidence: 94%
“…Myrosin cells are found along veins in Arabidopsis and other Brassicales plants [74][75][76]. Based on the close proximity of myrosin cells to vascular precursor cells and phloem cells [50,75,76], myrosin cells could belong to a vascular cell lineage and differentiate from vascular and vascular precursor cells. More recent studies, however, have provided evidence against this hypothesis.…”
Section: Development and Evolutionary Origin Of Myrosin Cellsmentioning
confidence: 99%
“…This observation provoked the question of whether myrosin cells differentiate from vascular precursor cells (procambium cells). Two groups compared the spatiotemporal expression patterns of a myrosin cell reporter and a procambium reporter and showed that myrosin cells do not differentiate from procambium cells and, rather, directly differentiate from ground meristem cells, which are stem cell-like cells in inner tissue ( Li and Sack, 2014 ; Shirakawa et al, 2016b ). Ground meristem cells are also mother cells of mesophyll cells and procambium cells.…”
Section: Myrosin Cells Versus Vascular Cellsmentioning
confidence: 99%